Formal Software Verification Measures Up: Verified coding techniques use mathematical proofs to ensure code is error-free and hacker-resistant. Can the approach revolutionize software? - Greengard, Samuel (Communications of the ACM, 2021)
The article examines whether the use of mathematical proofs in the process of verified coding can be applied to error-free coding and computer hacker resistance in order to improve and advance the development of computer software.